2023
DOI: 10.1002/cbdv.202200760
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α‐Glycosidase by Lippia dulcis Trevir. (Verbenaceae) Preparations, Quantification of Verbascoside, and Study of Its Molecular Docking

Abstract: This study aimed to quantify verbascoside (VEB), perform molecular docking studies of VEB with the αglucosidase (GL) of Bacillus stearothermophilus, and evaluate the inhibition of the enzyme by L. dulcis preparations. The substrate concentration and presence of reduced glutathione were evaluated for their effect on the in vitro inhibition of the GL enzyme. Assays were also performed in the presence and absence of simulated gastric fluid. The antidiabetic fractions 2 and 3 were the most inhibited GL, but their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Likewise, Boushehri et al [66] showed that HS sour tea consumption is associated with a significant reduction in fasting plasma glucose. Therefore, both the anthocyanins of HS, as well as verbascoside, isoverbascoside, and rosmarinic acid of LC, seem to have hypoglycemic effects [71][72][73][74]. One of the accepted mechanisms of action of these extracts is the improvement of insulin sensitivity, which is crucial for maintaining healthy blood glucose levels.…”
Section: Effect Of Hs In Combination With Other Plant Extracts On Blo...mentioning
confidence: 99%
“…Likewise, Boushehri et al [66] showed that HS sour tea consumption is associated with a significant reduction in fasting plasma glucose. Therefore, both the anthocyanins of HS, as well as verbascoside, isoverbascoside, and rosmarinic acid of LC, seem to have hypoglycemic effects [71][72][73][74]. One of the accepted mechanisms of action of these extracts is the improvement of insulin sensitivity, which is crucial for maintaining healthy blood glucose levels.…”
Section: Effect Of Hs In Combination With Other Plant Extracts On Blo...mentioning
confidence: 99%